The Impact of Discipline and Work Facilities on Motivation and its Impact on The Quality of the General Public Services in the Regional Financial and Asset Agency of West Tanjung Jabung Regency - Atiki, Alik; Zahari, M.; Hapsara, Osrita (Dinasti International Journal of Management Science, 2025)
This research objectives to ascertain discipline, work facilities, motivation, and the quality of The general public services at the Regional Finance and Assets Agency of West Tanjung Jabung Regency. It also analyzes the influence of discipline and work facilities on motivation and their impact on the quality of The general public services. This research was conducted at the Regional Finance and Assets Agency of West Tanjung Jabung Regency. The data used in this research were secondary and primary data. The sample size was 86 respondents. This sampling technique is known as saturated sampling. The data analysis method used was a descriptive and verification approach using Partial Least Squares (PLS) data analysis. The results of the descriptive analysis indicate that employee discipline is categorized as high. The work facilities used are in good condition. Employee motivation is categorized as high. The quality of The general public services provided is categorized as good. The results of the verification analysis indicate that discipline and work facilities have a positive and noteworthy impact on employee motivation. Discipline, work facilities, and motivation have a direct, positive and noteworthy impact on the quality of The general public services. Furthermore, motivation has been shown to mediate the influence of discipline and work facilities on the quality of The general public services. Therefore, it can be concluded that improving discipline and providing adequate work facilities can boost employee motivation, ultimately improving the overall quality of The general public services.